GAMIFICATION IN LEARNING ARCHITECTURE DESIGN WITH AUGMENTED REALITY - Nadia, Zaini; Sharon, Ting Yew Jia; Nurfauza, Jali; Mustafa, Payandenick; Suriati Khartini, Jali (ACADEMIA INDUSTRY NETWORKS, 2022)
Nowadays, gamification has been widely used in the educational environment. It is because gamification of education is a great approach for increasing learners’ engagement by incorporating game-like elementS or games into the learning process. The main aims to sustain gamification in education are to optimise learners' experience in their learning process, enrich their skills, and enhance motivation in studies. In addition, most of the learning materials are provided to learners through images, videos, and textbooks in the classroom. These learning materials will convey detailed theoretical knowledge of lessons to learners. Nevertheless, such a teaching method does not consider learners’ interpretation of the existing materials in the real environment, causing learners to lack diversity in studies. Moreover, there is another major problem in the current education system: instructors are more focused on providing traditional teaching methods that support learners reciting and memorising the syllabus, thus lacking emphasis on learners’ critical thinking. As a result, it can cause learners to become lack interest in studies and lead to a decline in academic performance. To solve the problem of less interest and lack of concentration in studies, various types of learning method and learning materials were investigated and analysed throughout this project to develop a mobile application to enrich students’ motivation. Furthermore, Augmented Reality (AR) technology will also be applied to this proposed mobile application to encourage learners' engagement in studies.